Дослідження впливу штанц-форм на якість вигляду дитячої літератури - Самсонова, Христина Василівна; Григор’єв, Олександр Вікторович (Eastern-European Journal of Enterprise Technologies, 2010)
General characteristic of punching forms. A comparative analysis of the most popular in Ukraine of punching forms and shows the results. The basic characteristics of punching forms that affect the quality of cutting and aesthetic appearance of the publication with the release of children’s literature